Efficacy of plant extracts in enhancing growth and molting of crab (Scylla serrata) in a traditional pond system - Esti Handayani Hardi; Andre Julpano; Wanda Rahmawati; Gina Saptiani; Ricko Reynalta; Endah Paramitha; Pande Gde Sasmita Julyantoro; Yuniarti Koniyo; Rudy Agung Nugroho (Egyptian Journal of Aquatic Research)
This study explores the impact of mixed plant extracts containing Boesenbergia pandurata, Solanum ferox, and Zingiber zerumbet on Scylla serrata crabs cultivated in traditional ponds. Crabs (450 crabs weighing 136 ± 8.5 g) were divided into five groups for four weeks, with three replicates. The five treatments involved a control without extract (P1), 20 (P2) and 30 (P3) mL/kg of the mixed extracts of S. ferox and B. pandurata, and 20 (P4) and 30 (P5) mL/kg of the mixed extracts of S. ferox and Z. zerumbet. The most favorable crab growth outcomes were observed in P3 (74.30 g), which also exhibited the highest molting percentage (100 %). The highest survival rate was observed in P2 (97.50 %). The dosage of 30 mL/kg of S. ferox and B. pandurata is appropriate for stimulating growth, average molting rate, and molting percentage. But, notably, both doses of all three studied extracts proved to be more effective than the control for enhancing growth, molting, and survival in crab culture. This study suggests that S. ferox, B. pandurata, and Z. zerumbet combination diets in crab culture in traditional ponds can improve crab growth, molting, and survival rates, enhancing animal welfare.